Activating Culture for Innovation: A Resource-Based Framework for Cultural Tourism Development in Indonesia - Mardhiyah, Ainun; Badaruddin, Badaruddin; Safrin, Feby Aulia (International Review of Management and Marketing, 2025)
This study investigates the role of Cultural Value Activation in fostering Destination Innovation, mediated by Cultural-Centric Innovation Capacity, within the context of cultural tourism development in North Sumatera, Indonesia. Drawing on the Resource-Based View (RBV), a conceptual model was developed and tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 233 respondents, including cultural actors, creative entrepreneurs, and tourism managers. The results confirm that Cultural Value Activation significantly influences both innovation capacity and destination innovation, with innovation capacity serving as a partial mediator. These findings highlight the strategic importance of cultural resources and organizational capability in driving innovation in heritage-based tourism destinations. The study offers theoretical contributions by integrating cultural heritage and innovation frameworks and provides practical implications for policy-makers and practitioners aiming to build agile and culturally grounded tourism development strategies.